BOARD OF DIRECTOR’S CHARACTERISTICS, INTELLECTUAL CAPITAL, AND BANK PERFORMANCE An empirical examination of Indonesian Banking Sector - Rositha, Annisa Hilmy; Firdausi, Nila; Darmawan, Ari (The International Journal of Accounting and Business Society, 2019)
Abstract The purpose of this study is to examine the effect of board of directors’characteristics on intellectual capital and bank performance. This research applies explanatory research with a quantitative approach. The data derived from secondary bank annual report data. The total sample consisted of 12 Indonesian Conventional Banks for a period of 3 years ranging from 2015 to 2017. Partial Least Square (PLS) Analysis is used to analyze the collected data. The results of this study indicated that the board of directors’ characteristics have a positive and significant influence on intellectual capital. Further testing, the board of directors’ characteristics has a positive and significant influence on bank performance. Intellectual Capital has a positive and significant influence on bank performance. Keyword: Corporate Governance, Board of Directors, Intellectual Capital, Bank    Performance, Indonesian Banking